Illocutionary Speech Acts of Articulating Commands in the Movie “Marvels”: An analysis of Linguistics Principles - Skolastika , I Made Perdana; Mahardika, Kadek Wisnu (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Speech acts play a crucial role in human communication, allowing individuals to perform actions through language. The application of speech act is crucial especially in communication because it is an action of communication. Therefore, this study investigates the various forms of illocutionary acts, with a particular emphasis on directive speech acts, as presented in the film